Microbial Succession in Spontaneously Fermented Grape Must Before, During and After Stuck Fermentation - Ultee, A.; Wacker, A.; Kunz, D.; Löwenstein, R.; König, H. (South African Journal of Enology and Viticulture, 2016)
The microbial succession in spontaneously fermenting Riesling must was investigated from the beginning (pressing) until the end (sulphuring) of the fermentation in two harvest years (2008 and 2009) at a Moselle winery (Germany). In both years, the fermentation was interrupted by a stuck period. The length of the stuck period varied considerably (20 weeks in 2008 and one week in 2009). Different yeasts (Candida, Debaryomyces, Pichia, Hanseniaspora, Saccharomyces, Metschnikowia, Cryptococcus, Filobasidium and Rhodotorula) and bacteria (Gluconobacter, Asaia, Acetobacter, Oenococcus, Lactobacillus, Bacillus and Paenibacillus) were isolated successively by plating. The main fermenting organism was Saccharomyces uvarum. Specific primers were developed for S. uvarum, H. uvarum and C. boidinii, followed by the determination of the total cell counts with qPCR. The initial glucose concentration differed between the two years and was 116 g/L in 2008 and 85.4 g/L in 2009. Also, the fructose concentrations were different in both years (114 g/L in 2008 and 77.8 g/L in 2009). The stuck period appeared when the glucose/fructose ratio was 0.34 and 0.12 respectively. The microbiota changed during the stuck period.